Assessment of economic development of central business districts – A combination multi-criteria evaluation methodology - Kaiyuan He; Bingbing Huang; Xinyu Liu; Shouzhen Zeng (PLoS ONE, 2025)
Background The economic development of central business districts (CBDs) is a key driver of urban economic growth and enhances regional competitiveness. However, existing research predominantly focuses on macro-level analyses, lacking systematic and quantitative indicator systems for detailed evaluation of CBD economic development performance, while studies on urban office buildings or specific CBD components often neglect the broader context of the entire district. Objectives This study aims to propose a multi-criteria evaluation system to effectively evaluate the economic development performance of CBDs, and provide theoretical references for a more comprehensive evaluation of the sustainable CBD growth in other regions. Methods Firstly, the analytic hierarchy process (AHP) and entropy method are proposed to determine combination weights for each indicator. The VlseKriterijumska Optimizacija Kompromisno Resenje (VIKOR) method is then introduced to rank the economic development performance of CBDs. Finally, a numerical example of Zhejiang province is carried out to validate the results by comparing its rankings with existing methods. Results and conclusion The multi-criteria evaluation of regional CBD economic development showed that the top two cities remained consistent across subjective, objective, and combined weights methods, while discrepancies in rankings for other cities were balanced by the combined weights approach. Meanwhile, minor variations in rankings highlighted the unique advantages of each method. These findings validate the effectiveness of combining subjective and objective methods for assessments. Future research should enhance data comprehensiveness and reliability through fieldwork to further improve the scientific validity of such evaluations.